Light on peacemaking : a guide to appropriate dispute resolution and mediating family conflict - DiGrazia, Thomas (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Many books have been written about the practice of peacemaking, and few, if any, contribute to the non-violent, spiritual side of this ancient science, discipline, practice and art form. This book speaks to that lack and explores the spiritual, non-violent element in peacemaking as it applies to appropriate dispute resolution and mediating family law disputes. Universities will find the book helpful as a textbook in their peacemaking and mediation degree and certificate programs. This book is intended for the professional peacemaker, mediator, lawyer, law student, conciliator, and dispute neutral. Everyday people wishing to improve their own communication skills and strengthen their primary relationships will profit greatly from this book. Those in the family law field, will find much benefit from the peacemaking processes, family counseling psychology, Eastern philosophy and Yoga, collected wisdom, experience and practice pointers presented in Light on Peacemaking. Mental health family practitioners, who are often called upon to act as default, if not, formal mediators and neutrals, will find useful the mediation and peacemaking experiences, techniques and literature related here. Light on Peacemaking also offers the Yoga practitioner a very practical avenue, through example in the legal field, for engaging in seva or service to humanity.
Part I. Introduction -- 1. Thumbnail sketch of appropriate dispute resolution history -- 2. ADR processes -- 3. Appropriateness of process in mediation -- 4. Conflict and brain science -- Part II. Methods -- 5. Some peacemaking tools for dealing with conflicted divorce -- 6. Mediation skills and techniques -- 7. Negotiations -- Part III. Advanced issues -- 8. When people are the issues--a further word about difficult mediation conversations -- 9. Some last resort options -- 10. Conclusions -- References -- Index.
Includes bibliographical references (pages 191-196) and index.
Title from PDF title page (viewed on November 25, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Dispute resolution (Law); Reconciliation; Mediation; Family mediation; ADR processes; adversarial; alimony; alternative dispute resolution; appropriate dispute resolution; B.K.S. Iyengar; brain science; child support; children; collaborative law; conflict; conscious uncoupling; counseling; courts; difficult conversations; divorce; Eastern philosophy; educated divorce; evaluative; facilitative; family counseling; family court; family law; interdisciplinary team; J. Krishnamurti; law; law student; lawyers; legal system; litigation; marital dissolution; mediation; mediation participants; mediation skills and techniques; mediator; mental health professional; mindfulness; Native Americans; negotiations; neutral; nonviolence; peacemaker; peacemaking; peacemaking algorithm; post-traumatic stress disorder (PTSD); psychologists; psychology; seva (service to humanity) and ahimsa (do no harm); spiritual; students; seva; transformation; violence; yoga; Yoga Sutra; Electronic books